Circumferential endoscopic submucosal dissection of a 14-cm long-segment Barrett’s esophagus with multifocal adenocarcinoma: a case report - Aida Saad, MD; Joyce Arnouk, MD; Arshia Khorasani-Zadeh, MD; Monika Seth, MD; Kais Zakharia, MD (VideoGIE)
Background and Aims: Barrett's esophagus (BE) is a recognized precursor to esophageal adenocarcinoma (EAC), with an annual progression risk of up to 7% in cases involving high-grade dysplasia (HGD). Endoscopic therapy is the standard treatment for dysplastic BE and early-stage EAC, typically involving ablation techniques, such as radiofrequency ablation and cryotherapy, for flat BE and endoscopic resection methods, including EMR and more recently endoscopic submucosal dissection (ESD), for nodular lesions. Methods: This article describes the case of a patient with an ultralong segment of BE (14 cm) and multifocal EAC who was successfully treated with circumferential ESD. Results: A complete en bloc resection of a 16-cm segment was achieved. Histopathologic analysis confirmed the presence of BE with HGD and multifocal EAC (T1b). Although the patient developed an esophageal stricture postprocedure, it was effectively managed endoscopically. Conclusions: The patient is currently doing well and remains under routine endoscopic and radiographic surveillance. Circumferential ESD represents a safe and effective approach for the endoscopic resection of extensive BE and early EAC and should be considered a viable alternative to surgical intervention.